Pelatihan “Lingkungan Media Sosial Kontemporer: Tantangan Dan Peluangnya” Bagi Perempuan Wirausaha Di Wilayah Jabodetabek - Ezmieralda Melissa; Muninggar Sri Saraswati; Fajrie Samahita (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
One group that has the potential to boost entrepreneurship, but is often undervalued is women. Although they consist of approximately sixty per cent of all entrepreneurs in Indonesia, they often face more challenges in comparison to male entrepreneurs in conducting their business ventures. These challenges include limited access to funding, multiple roles and responsibilities in the family and society, limited knowledge of information and communication technologies, and inadequate support system. Many women turn to social media to enable them opening a business that they can manage from home. While generally social media bring positive consequences to these woman entrepreneurs, the dynamic of the social media environment means that these women have to face obstacles to keep up with the technological developments and the changes of interactions that they bring to the business conducts and sellers-consumer interactions. This community service program aimed to provide capacity building training which focuses on women who own online micro businesses. Through this community service program, we introduced participants to the potential challenges that are brought by the changes in the social media environment. At the same time, we also assisted them in planning an effective social media communication plan that can help them to overcome these challenges. This workshop also allowed participants to network with other woman entrepreneurs that can potentially increase their social capital.